Aneuploidy in sperm of fertile men and patients with impaired fertility - A. O. Sedova; A. I. Martemyanova; V. B. Chernykh (Андрология и генитальная хирургия, 2021)
The review presents generalized current data on sperm aneuploidy in healthy (fertile) men and infertile male patients with a normal karyotype and with chromosomal abnormalities. The mechanisms of aneuploidy in germ cells, factors affecting of its level, the relationship with defects of spermatogenesis, meiosis, decreased sperm parameters, as well as the effect of sperm aneuploidy on male fertility, embryo development and gestation are discussed.